Role of Folic Acid, Vitamin D, and Progesterone in Pregnancy and Threatened Abortion - Jassim, Shaimaa; Raid M. H. Al-Salih (University of Thi-Qar Journal of Science, 2023)
The most frequent early pregnancy problem threatened abortion, affects 20% of pregnancies. Vaginal bleeding may be present, together with or without abdominal cramps. Women who are getting older, smoking, being overweight or obese, having PCOS, and having had an abortion in the past are danger signs for a potential abortion. The Physiology of the disease has been linked to alterations in cytokine concentrations or weakened maternal immunity. By taking the clinical history into account, determine the therapy options and provide crucial information for the prognosis, the physical examination, the biochemistry of the mother’s serum, and the results of the ultrasound. The most popular advice is to stay in bed, but its usefulness is not well supported. Progesterone, vitamin D, and folic acid are further alternatives.